Respuesta :

Answer:

x=1

Step-by-step explanation:

266300

Answer:

x = 1

Step-by-step explanation:

Step 1: Simplify both sides of the equation.

2.3x −3.2 + 1.6x = 0.7x

2.3x + − 3.2 + 1.6x = 0.7x

(2.3x + 1.6x) + (−3.2 )= 0.7x (Combine Like Terms)

3.9x + −3.2 = 0.7x

3.9x − 3.2 = 0.7x

Step 2: Subtract 0.7x from both sides.

3.9x − 3.2 − 0.7x = 0.7x − 0.7x

3.2x − 3.2 = 0

Step 3: Add 3.2 to both sides.

3.2x − 3.2 + 3.2 = 0 + 3.2

3.2x = 3.2

Step 4: Divide both sides by 3.2.

x = 1

Hope this helps!!!!!